Mythical relationship between the Jami's Haft Orang and Nizami's Khamse - Mohammad Reza Hassan iJalilian, Saeed Emami, Ghasem Sahraei, Ali Heidari, (Opción, 2019)
In this article, it is tried to examine the manifestation and the relationship between ugliness and devastation in two sets of Jami's Haft Orang and Nizami's Khamse. According to our studies, it has become clear to us that the mystical text of Haft Orang has revealed much less of this relationship due to the monotheistic spirit of its versified story. But in the versified stories of Nizami's Khamse,there are moreexamples and manifestations in connection with the relationship between ugliness and devastation, and therefore, Nizami's Khamse is a better reflection of Iranian mythical and folklore beliefs.